Pharmacological perturbation of CXCL1 signaling alleviates neuropathogenesis in a model of HEVA71 infection - Saravanan, Gunaseelan; Mohammed Zacky, Ariffin; Sanjay, Khanna; Mong, How Ooi; Perera, David; Chu, Justin Jang Hann; Chua, John Jia En (Springer Nature, 2022)
Hand, foot and mouth disease (HFMD) caused by Human Enterovirus A71 (HEVA71) infection is typically a benign infection. However, in minority of cases, children can develop severe neuropathology that culminate in fatality. Approximately 36.9% of HEVA71-related hospitalizations develop neurological complications, of which 10.5% are fatal. Yet, the mechanism by which HEVA71 induces these neurological deficits remain unclear. Here, we show that HEVA71-infected astrocytes release CXCL1 which supports viral replication in neurons by activating the CXCR2 receptor-associated ERK1/2 signaling pathway. Elevated CXCL1 levels correlates with disease severity in a HEVA71-infected mice model. In humans infected with HEVA71, high CXCL1 levels are only present in patients presenting neurological complications. CXCL1 release is specifically triggered by VP4 synthesis in HEVA71-infected astrocytes, which then acts via its receptor CXCR2 to enhance viral replication in neurons. Perturbing CXCL1 signaling or VP4 myristylation strongly attenuates viral replication. Treatment with AZD5069, a CXCL1-specific competitor, improves survival and lessens disease severity in infected animals. Collectively, these results highlight the CXCL1-CXCR2 signaling pathway as a potential target against HFMD neuropathogenesis.